2014
DOI: 10.3409/fb62_1.9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation in Alymphoplasia (<I>aly</I>/<I>aly</I>) Mice

Abstract: Bacterial translocation (BTL) is defined as the passage of viable bacteria from the gastrointestinal tract to the organs. This study was to elucidate the roles of Peyer's patches (PPs) and/or mesenteric lymph nodes (MLNs) in BTL. Alymphoplastic mutant mice and phenotypically normal heterozygous micewere dominantly colonized with streptomycin-resistant Escherichia coli and BTL was examined. In PP- and MLN-competent mice, BTL to MLNs was detected in 100% of mice, but BTL to organs was rare (25%). On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is well established that activation of TLRs by their agonists significantly enhances the internalisation of bacteria in both professional immune cells, such as macrophages (Blander and Medzhitov, 2004;Doyle et al, 2004), and non-professional immune cells, such as intestinal epithelial cells (Neal et al, 2006). In addition to this, E. coli C25 has been used as a model strain for bacterial translocation through the intestinal epithelial barrier (Clark et al, 2003;Macutkiewicz et al, 2008;Suzuki and Okada, 2014); therefore, we decided to explore the regulatory effects of OMVs on this process. Consequently, we demonstrate that pretreatment with C25 OMVs was able to reduce the subsequent internalisation of the C25 bacterium in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that activation of TLRs by their agonists significantly enhances the internalisation of bacteria in both professional immune cells, such as macrophages (Blander and Medzhitov, 2004;Doyle et al, 2004), and non-professional immune cells, such as intestinal epithelial cells (Neal et al, 2006). In addition to this, E. coli C25 has been used as a model strain for bacterial translocation through the intestinal epithelial barrier (Clark et al, 2003;Macutkiewicz et al, 2008;Suzuki and Okada, 2014); therefore, we decided to explore the regulatory effects of OMVs on this process. Consequently, we demonstrate that pretreatment with C25 OMVs was able to reduce the subsequent internalisation of the C25 bacterium in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies utilising live C25 have demonstrated its ability to translocate through the intestinal epithelial barrier (Clark et al, 2003;Macutkiewicz et al, 2008;Suzuki and Okada, 2014) and to initiate a proinflammatory response in intestinal epithelial cell lines (Michalsky et al, 1997;Clark et al, 2003;Zareie et al, 2005;Macutkiewicz et al, 2008). …”
Section: Introductionmentioning
confidence: 99%